2018
DOI: 10.11648/j.wjfst.20180202.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Frying on Acrylamide Formation in Potato Chips

Abstract: The occurrence of acrylamide, a probable carcinogen and a neurotoxin, is currently a global issue. Therefore, the main objective of the present study was to determine the effects of microwave frying on acrylamide formation in potato chips. A simple method using high-performance liquid chromatography has been applied for determination of acrylamide in microwave-fried potato chips. The results showed that microwave frying could form more acrylamide at high microwave power level 800 W compared with low microwave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…On the other hand, MF for 160 seconds at a temperature of 180 °C showed lower acrylamide content. This finding is consistent with the research by Elfaitouri [38], who observed that frying potato chips in corn oil at lower These findings contribute to the understanding of the trade-offs between health considerations and sensory appeal when selecting a frying method for French fries.…”
Section: Carbohydrate Contentsupporting
confidence: 91%
“…On the other hand, MF for 160 seconds at a temperature of 180 °C showed lower acrylamide content. This finding is consistent with the research by Elfaitouri [38], who observed that frying potato chips in corn oil at lower These findings contribute to the understanding of the trade-offs between health considerations and sensory appeal when selecting a frying method for French fries.…”
Section: Carbohydrate Contentsupporting
confidence: 91%